Antibody-based delivery of interleukin-2 modulates the immunosuppressive tumor microenvironment and achieves cure in pancreatic ductal adenocarcinoma syngeneic mice - Carmine Carbone; Roberto De Luca; Emanuele Puca; Antonio Agostini; Alessia Caggiano; Lorenzo Priori; Annachiara Esposito; Serena Ascrizzi; Geny Piro; Lisa Salvatore; Francesco De Sanctis; Stefano Ugel; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and deadly type of cancer, with an extremely low five-year overall survival rate. To date, current treatment options primarily involve various chemotherapies, which often prove ineffective and are associated with substantial toxicity. Furthermore, immunotherapies utilizing checkpoint inhibitors have shown limited efficacy in this context, highlighting an urgent need for novel therapeutic strategies. This study investigates the preclinical efficacy of an innovative targeted therapy based on antibody-cytokine fusion proteins, specifically interleukin-2 (IL-2), a pivotal driver of cell-mediated immunity, fused to L19 antibody, which selectively binds to extra domain B of fibronectin (EDB-FN1) expressed in the tumor microenvironment. Methods We tested the effectiveness of different immunocytokines through in vivo characterization in syngeneic C57BL/6J orthotopic mouse models of PDAC. Based on these results, we decided to focus on L19-IL2. To assess the efficacy of this immunocytokine we developed an ex-vivo immune-spheroid interaction platform derived from murine 3D pancreatic cultures, and telomerase reverse transcriptase (TERT) specific T-lymphocytes. Moreover, we evaluated the anti-cancer effect of L19-IL2 in combination with standard therapy in vivo experiments in PDAC mouse models. Tumor samples collected after the treatments were characterized for tumor infiltrating immune cell components by bulk RNA sequencing (RNA-seq) and spatial transcriptomics (Stereo-seq) analysis. Results The tumor-targeted L19-IL2 fusion protein demonstrated potent, dose-dependent anti-tumor activity in mice with pancreatic tumors resistant to standard chemotherapy. Spatial Transcriptomics (ST) and RNA-seq analyses indicated that L19-IL2 treatment induced a significant influx of immune cells into the tumor microenvironment, with these cells expressing activation markers like granzymes, perforins, and the IL-2 receptors. Conclusions Our results demonstrated that L19-IL2 enhances immune infiltration and cytotoxicity, remodeling the “cold” tumor microenvironment (TME) in PDAC. This innovative antibody-cytokine fusion protein improves therapeutic outcomes, paving the way for novel targeted treatment strategies in PDAC.